Does multiple sclerosis increase the risk of preeclampsia? A systematic review and meta-analysis - Ahmed Arafa; Xiaowen Wang; Jia-Yi Dong; Ehab S Eshak (Hypertension in Pregnancy, 2021)
Objective: We investigated, via systematic review and meta-analysis, whether multiple sclerosis (MS) is associated with the risk of preeclampsia (PE). Methods: From the eligible studies, we pooled odds ratios (ORs) and confidence intervals (CIs) of PE for pregnant women with MS compared with pregnant women without it using the fixed-effects model. The I2 measured heterogeneity between studies. Results: Eight eligible studies (9 cohorts) were included. Pregnant women with MS had no excess risk of PE compared with pregnant women without MS (pooled OR = 0.99, 95% CI: 0.89, 1.09; I2 = 0.00%). Conclusion: MS is not associated with PE.